An ethanol-based fixation method for anatomical and micro-morphological characterization of leaves of various tree species. (February 2013) - Chieco, C; Rotondi, A; Morrone, L; Rapparini, F; Baraldi, R
Abstract The use of formalin constitutes serious health hazards for laboratory workers. We investigated the suitability and performance of the ethanol-based fixative, FineFIX, as a substitute for formalin for anatomical and cellular structure investigations of leaves by light microscopy and for leaf surface and ultrastructural analysis by scanning electron microscopy (SEM). We compared the anatomical features of leaf materials prepared using conventional formalin fixation with the FineFIX. Leaves were collected from ornamental tree species commonly used in urban areas. FineFIX was also compared with glutaraldehyde fixation and air drying normally used for scanning electron microscopy to develop a new method for evaluating leaf morphology and microstructure in three ornamental tree species. The cytological features of the samples processed for histological analysis were well preserved by both fixatives as demonstrated by the absence of nuclear swelling or shrinkage, cell wall detachment or tissue flaking, and good presentation of cytoplasmic vacuolization. In addition, good preservation of surface details and the absence of shrinkage artefacts confirmed the efficacy of FineFIX fixation for SEM analysis. Cuticular wax was preserved only in air dried samples. Samples treated with chemical substances during the fixation and dehydration phases showed various alterations of the wax structures. In some air dried samples a loss of turgidity of the cells was observed that caused general wrinkling of the epidermal surfaces. Commercial FineFIX is an adequate substitute for formalin in histology and it can be applied successfully also for SEM investigation, while reducing the health risks of glutaraldehyde or other toxic fixatives. To investigate the potential for plants to absorb and capture particulates in air, which requires preservation of the natural morphology of trichomes and epicuticular waxes, a combination of FineFIX fixation and air drying is recommended.